2019
DOI: 10.13057/biodiv/d200540
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal species diversity and density of cryptic crustacean (Brachyura and Anomura) in micro-habitat Autonomous Reef Monitoring Structures across Kepulauan Seribu, Indonesia

Abstract: Abstract. Hazeri G, Rahayu DL, Subhan B, Sembiring A, Anggoro AW, Ghozali AT, Madduppa HH. 2019. Latitudinal species diversity and density of cryptic crustacean (Brachyura and Anomura) in micro-habitat Autonomous Reef Monitoring Structures across Kepulauan Seribu, Indonesia. Biodiversitas 20: 1466-1474. Kepulauan Seribu is located in the north of Jakarta and has historically been affected by anthropogenic activities. Based on its anthropogenic pressure, the archipelago is divided latitudinally into three main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…ARMS have thus been increasingly applied over the last decade to research rocky habitats in different regions (e.g. east coast of the USA (Leray & Knowlton, 2015); Red Sea (Carvalho et al., 2019; Pearman et al., 2016, 2019); French Polynesia (Ransome et al., 2017); Gulf of Aqaba (Al‐Rshaidat et al., 2016), Indonesia (Hazeri et al., 2019) and European waters (David et al., 2019; Pennesi & Danovaro, 2017)). The combination of a standardized tool for sampling biodiversity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…ARMS have thus been increasingly applied over the last decade to research rocky habitats in different regions (e.g. east coast of the USA (Leray & Knowlton, 2015); Red Sea (Carvalho et al., 2019; Pearman et al., 2016, 2019); French Polynesia (Ransome et al., 2017); Gulf of Aqaba (Al‐Rshaidat et al., 2016), Indonesia (Hazeri et al., 2019) and European waters (David et al., 2019; Pennesi & Danovaro, 2017)). The combination of a standardized tool for sampling biodiversity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Crab biota utilizes dead corals as a refuge from epibenthic and nektonic organisms. In Tidung Besar, the relative absence of anthropogenic interference with coral reef ecosystems was characterized by large number the family Porcellanidae is commonly found in bottom sandy substrate with coral rubble (Hazeri et al, 2019). This demonstrated that Porcellanidae could be easily discovered in many areas compared to other family of Anomura Chlorodiella nigra is the species with the largest percentage contribution and has a distribution pattern that tends to spread throughout the tropical Indo-Pacific region as well as in the Gulf of Kach, India (Beleem et al, 2014) (Figure 5a).…”
Section: Anthropogenic Factors On Diversity Of Cryptic Crustaceanmentioning
confidence: 99%
“…Furthermore, abundant algae and other encrusting organisms such as ascidians and sponges usually colonized the structure of the coral head (Kramer et al, 2017). Dead coral colonies have also been identified as a microhabitat for some invertebrate organisms including crustaceans (Kramer et al, 2014;Hazeri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, there was increasing species richness in the middle of the stream along the longitudinal gradient ( Figure 5). Hazeri et al (2019) reported that crustacean species depend on the availability of habitat structure. In detail, Silva-Junior et al (2017) reported that decapods were more abundant in leaf litter substrates than in sandy areas.…”
Section: Longitudinal Distributionmentioning
confidence: 99%